Employee Satisfaction and Work Discipline Affecting Job Performance of Tour Guides in Southern Thailand - Keawsawat , Benchawan; Jankingthong, Wiwat; Jedsarid , Jedsarid (Ph.D. in Social Sciences Journal, 2026)
This research article aims to (1) study the confirmatory components of work efficiency among tour guides in southern Thailand and (2) examine the influence of employee satisfaction and work discipline on the work efficiency of tour guides in southern Thailand. It is quantitative research. A sample group of 400 tour guides working in travel companies in southern Thailand. The data were collected using a questionnaire with reliability values of 0.946 for work efficiency, 0.972 for employee satisfaction, and 0.978 for work discipline. Hypotheses were tested using multiple regression analysis and confirmatory factor analysis. The research findings revealed that (1) the confirmatory factor analysis of work efficiency among tour guides in southern Thailand showed external component loadings ranging from 0.927 to 0.984. The factor coefficients for all variables were statistically significant at the 0.01 level, with SRMR = 0.02, NFI = 0.95, dULS = 0.21, and dG = 0.12, which met the established criteria. (2) Employee satisfaction and work discipline had a statistically significant influence on the work efficiency of tour guides in southern Thailand at the 0.1 level, with coefficients of 0.396 and 0.528, respectively.